Digital tourism advertisements in social media sites and their role in the electronic marketing mix (An exploratory study of the sample of travel companies traveling in Baghdad) - hameed salim, Salim; F .Mustafa, Rasha (International Journal of Psychosocial Rehabilitation, 2020)
Technological development has taken a large area of interest, and application of business in a wide range, especially tourism activities, including tourism advertising in social media, has been reflected in the mix of electronic marketing of tourism businesses, as this research paper aims to verify the role of digital tourism advertising in the electronic marketing mix and identify criteria for evaluating the digital content of tourism advertisements for travel and tourism companies. The researcher adopted a hypothetical model that illustrates the relationship and impact between the dimensions of digital tourism advertisements and the electronic marketing mix. The researcher relied on the descriptive analytical method. The sample of the study reached 56 officials on the promotional activity in the travel and tourism companies. The relationship between the digital tourism advertisements and the characteristics of the promotional electronic tourism mix was positive, and the results of the research reflected a set of recommendations, the most important of which is the need for the researched companies to recognize the importance of the dimensions and features of digital advertising. Digital tourism and conditions for the purpose of providing electronic marketing mix.